Recent mineral discoveries on Windy Arm, Tagish Lake, Yukon [electronic resource] - McConnell, R. G. (Richard George), 1857-1942.; Geological Survey of Canada. (Ottawa : S.E. Dawson, 1905)
At head of title: Geological Survey of Canada . Electronic reproduction. Mode of access: Internet. 44